PRODUCTION OF HEAT-INSULATING MATERIAL BASED ON AGRICULTURAL WASTE - Akhmedov Islombek; F.Dadaxanov (Journal of new century innovations, 2023)
Abstract. The article deals with the use of agricultural waste as a filler for gypsum thermal insulation materials, the compositions and properties of these materials are considered.